If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(z+4)=4(2z-1)
We move all terms to the left:
2(z+4)-(4(2z-1))=0
We multiply parentheses
2z-(4(2z-1))+8=0
We calculate terms in parentheses: -(4(2z-1)), so:We get rid of parentheses
4(2z-1)
We multiply parentheses
8z-4
Back to the equation:
-(8z-4)
2z-8z+4+8=0
We add all the numbers together, and all the variables
-6z+12=0
We move all terms containing z to the left, all other terms to the right
-6z=-12
z=-12/-6
z=+2
| 8^{e+2}+2=66 | | 6s(13+7)=0 | | 5(y-6)=-15 | | 5v+10=180 | | 11a+79+57=180 | | x/0.86=132 | | b-81/8=128/9 | | 33+35+7z=180 | | 31=x/2+10 | | 1.24x=8.68 | | x=30=-x=8 | | 6x2-15=21+2x2 | | 2u+8=38 | | |-5x+5|=45 | | |-5n+5|=45 | | 15x-3+2x*2=63,5 | | 1.28x=10.24 | | 40+8.50x=163.75 | | 4.7x-10.8=22.1 | | 6/7x+25/7=-11/7 | | 1-4m=-3m+7 | | 1-v=13+5v | | 20+2/3m=75 | | 5/4+1/2=2x-1/2 | | -12+2n=n-4= | | 3x+4=6 | | 63=7(-9+r) | | 3.2x-5=5-1.8x | | 50=-9v-4 | | 6=a/4+2= | | 2x-7=3x(1) | | x-94=9(2x+3)-15 |